Du tableau à la scène : la couleur dans le jardin paysager en France - Ilona Woronow (Projets de Paysage)
Theorists of the XVIIIth-century French landscape garden readily appeal to painting as a model for their art. The garden-architect is obliged to explore divers pictorial means, one of which is colour. Meanwhile, since colour within the neoclassical movement connoted bariolage and coquetterie, a redefinition became necessary for its integration is the landscape garden. Therefore, conceived as a visual quality, colour is admitted in panoramic views or as an educational device. In scenes depicting sensual pleasures, colour acquires other physical qualities, like material texture or odor. Finally, in other contexts, the couleur being marginalized, the visual qualities are perceived in terms of light nuances. Exploration with chiaroscuro relates the art of gardens to theater.